2019
DOI: 10.1002/arch.21548
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial reproductive manipulators in rice planthoppers

Abstract: Rice planthoppers (Hemiptera: Delphacidae) are notorious pests for rice (Oryza sativa) in Asia, posing a serious threat to rice production and grain security. Rice planthoppers harbor diverse bacterial symbionts, including Wolbachia, Cardinium, Spiroplasma, and Arsenophonus, which are known to manipulate reproduction in arthropod hosts. This microreview is to introduce current knowledge of bacterial reproductive manipulators in rice planthoppers, including their diversity, population dynamics, localization, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
(115 reference statements)
1
11
0
Order By: Relevance
“…The detection of symbionts in reproductive tissues (especially ovaries) indicates their maternal transmission. Indeed, symbionts like Wolbachia and Cardinium are vertically transmitted among rice planthoppers (Bing et al, 2019). The bacterial abundance was similar among different tissues in L. striatellus and S. furcifera, while the fungal abundance was significantly different.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The detection of symbionts in reproductive tissues (especially ovaries) indicates their maternal transmission. Indeed, symbionts like Wolbachia and Cardinium are vertically transmitted among rice planthoppers (Bing et al, 2019). The bacterial abundance was similar among different tissues in L. striatellus and S. furcifera, while the fungal abundance was significantly different.…”
Section: Discussionmentioning
confidence: 98%
“…Cardinium appears to have no effect on the fecundity of females, but hastens nymphal development (Zhang et al, 2012b). Importantly, Cardinium induces CI and is the leading factor of CI in S. furcifera when co-infected with Wolbachia (Nakamura et al, 2012;Zhang et al, 2012a;Bing et al, 2019). Intracellular symbionts influence the rest of the microbiome (Fromont et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Wolbachia is a reproductive symbiont in the insects (Stouthamer et al, 1999). However, high relative abundance of Arsenophonus might play a role in killing males (Bing et al, 2019), leading to the high ratio of female/male in the Kaifeng populations. These bacteria may promote insect growth and reproduction by influencing the different metabolic functions that the insects need to survive in the local environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that endosymbiotic bacteria can manipulate reproduction in other leafhoppers and planthoppers. In the planthoppers Laodelphax striatellus (Fallen, 1826) and Sogatella furcifera (Horvath, 1899) (Hemiptera: Delphacidae), Wolbachia and Cardinium induce cytoplasmic incompatibility between infected and uninfected hosts (Noda 1984, Hoshizaki and Shimada 1995, Noda et al 2001, Nakamura et al 2012, Zhang et al 2012, Bing et al 2019. In leafhoppers of the genus Zyginidia Haupt, 1929 (Hemiptera: Cicadellidae), Wolbachia can skew sex ratio toward females by feminizing genetically determined males (Negri et al 2006) and may be responsible for the production of intersex individuals in Eupteryx Curtis 1829 leafhoppers (Hemiptera: Cicadellidae) (Henke et al 2013).…”
mentioning
confidence: 99%